Protocol for live-cell imaging of immune synapse formation and activation of CAR T cells against cancer cells - Jorge Ibanez; Nikhil Hebbar; Unmesha Thanekar; Zhongzhen Yi; Haley Houke; Meghan Ward; Chris Nevitt; Liqing Tian; Stephen C. Mack; Heather Sheppard; Jason Chiang; M. Paulina Velasquez; et al. (STAR Protocols, 2024)
Summary: Immune synapse (IS) formation determines T cell antitumor activity. Here, we present a protocol for characterizing the IS formation between chimeric antigen receptor (CAR) T cells and tumor cells by measuring the IS size and calcium flux by live-cell imaging. We describe steps for CAR T cell manufacturing, sample preparation, image acquisition, and data analysis.For complete details on the use and execution of this protocol, please refer to Chockley et al.,1 Ibanez et al.,2 and Zoine et al.3 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.